The Relationship Between Company Returns and Leverage Depending on the Business Sector: Empirical Evidence from the Czech Republic - Stryckova Lenka (Journal of Competitiveness, 2017)
The paper aims to provide up-to-date empirical evidence of relationship between the key indicators of business competitiveness: leverage and corporate performance. The study is based on corporate financial data of selected companies from the Czech Republic within 14 major business sectors according to CZ-NACE which companies published for the year 2014. The results of this study show that leverage (debt ratio) has a substantially negative effect on corporate performance when the return on equity (ROE) is used as an indicator of corporate performance in the Czech Republic over the period covered by the study. The results of the regression analysis confirmed negative relationship between the company profitability and the use of debt in majority of business sectors (Agriculture, fishery, and forestry; Construction, Wholesale and retail trade, repair of motor vehicles and motorcycles; Professional, scientific and technical activities; Administrative and support service activities). The opposite relationship was found in one business sector only (Mining and quarrying) where positive relationship between the company profitability and leverage was confirmed. Among other things, the results of this study confirm that corporate leverage varies across industries.